PFM:a SMS4 algorithm against high-order power analysis attacks - LI Lang1; LI Ren-fa1; LI Jing1; WU Ke-shou3 (Tongxin xuebao)
A fixed-value mask algorithm for SMS4 was proposed in order to resist power analysis attack based SMS4.Firstly,an atomic mask algorithm of SMS4 was designed to resist against high-order power analysis attack based on the study of the structure of SMS4 algorithm,the intermediate variables were masked in the method.Secondly,pseudo-random fixed-value mask method（PFM） was proposed based on the above method,when its hardware implementation aiming at low power and less areas was considered about.Moreover,PFM has the ability to resist against high-order power analysis attacks when applied to the sensor node of special environment of communication.Finally,the experimental results show that the proposed algorithm has the ability to effectively resist second high-order differential power analysis attack without increasing much power and hardware resources.